A review on MRAS-type speed estimators for reliable and efficient induction motor drives. (October 2019) - Korzonek, Mateusz; Tarchala, Grzegorz; Orlowska-Kowalska, Teresa
Abstract: Induction machines have recently been very popular in variable-speed drives, because of their robust construction and relatively low manufacturing costs (brushless), maintenance-free and well-matured control methods. However, for high-precision control and efficiency optimization one needs the information on the rotor speed which can be measured using different speed sensors. All sensors require a mounting space and cabling, they also generate extra costs and reduce system reliability. Therefore, many of the recent research efforts have been dedicated to sensorless or encoderless electrical drives offering such considerable advantages as: lower cost, reduced size and hardware complexity of the drive system, elimination of sensor cables, lower maintenance requirements, possible operation in aggressive environment, higher noise immunity, reliable and user friendly operation. In this article all well-known sensorless techniques are shortly addressed, but the main focus is on the solutions based on the Model Reference Adaptive System (MRAS) concept. The mathematical models and schemes of all types of MRAS-type speed estimators known from the literature are gathered in this article. The comparative analysis of these speed estimators is done from the following points of view: the speed adaptation mechanism derivation based on the Lyapunov theory, stability problems near zero speed and in the regenerating operation mode, and the sensitivity of MRAS estimators to induction machine parameter changes. Highlights: Comprehensive review on IM speed estimation methods focused on MRAS techniques. Analysis of speed adaptation algorithms for different MRAS estimators. Consideration and comparison of stability regions of selected MRAS-based techniques. Overview of the stability improvement methods for speed estimators. Comparison of IM parameters mismatch robustness of speed estimators.